A Comparison of the Strength of Association of Reid Colposcopic Index and Swede Score With Cervical Histology. Issue 1 (January 2017) - Ranga, Renu; Rai, Shweta; Kumari, Aruna; Mathur, Sandeep; Kriplani, Alka; Mahey, Reeta; Agarwal, Nutan; Kachhawa, Garima; Vanamail, Perumal; Bhatla, Neerja
Abstract : Objective: Colposcopic scoring systems provide an objective diagnosis and select patients who require treatment. A new scoring system, Swede score, has added lesion size as a parameter. This study aimed to compare the strength of association of Reid colposcopic index versus Swede score and assess their utility in low-resource settings. Methods: In this prospective study, 150 women aged 30 to 59 years with abnormal screening result were enrolled. All women underwent colposcopy; the findings were scored by both Reid colposcopic index and Swede score, biopsy taken from all abnormal areas. Performances of both the scores were calculated. Results: A total of 33 (22%) CIN 2+ lesions were detected. Reid colposcopic index at a cutoff of 5 had sensitivity, specificity, positive predictive value, and negative predictive value for detecting CIN2+ lesions of 96.97%, 95.35%, 88.89%, and 98.8%, respectively. Using Swede score at a cutoff of 8, sensitivity, specificity, positive predictive value, and negative predictive value were 42.42%, 100%, 100%, and 81.9%, and with a cutoff of 5, these were 100%, 88.37%, 76.74%, and 100%, respectively. The correlation coefficient ( R 2 ) was 0.919. By Spearman rank correlation coefficient, the strength of correlation between Swede score and RCI was 0.937 ( p < .001). Conclusions: Swede score can be used flexibly depending on the setting. The lower threshold (5) with high sensitivity can be used for screening, whereas the higher threshold (8) with high specificity can be used for screen-and-treat selection to decrease the overtreatment rate. Thus, it is a more attractive option for cancer prevention programs in low-resource settings. Abstract : Swede score might be an alternative cervical cancer screening method in low-resource settings, enabling the screen and treat approach and avoiding overtreatment.